Audiovisual e o ensino de História: a análise fílmica e a busca de uma educação decolonial - MACHADO, Ivana de Paula de Araújo (2023)
In this article we aim to make a critical analysis about the use of audiovisual for the teaching of History in Basic Education. For this, we used an integrative literature review as a methodology. Throughout the research, a tendency was found to use audiovisuals only as entertainment without a deep critical reflection, transforming them into an instrument of colonization of mentalities. In this perspective, we present the Film Analysis methodology as an effective proposal for the use of audiovisual in the Teaching of History and its interface with decolonial thinking, proved to be a promoter for an addition to a Teaching of History that guides an emancipatory education. Within this, it is proposed to present and demonstrate that the union between Film Analysis and decolonial thinking, is structured as an excellent alternative to teachers who aim for the use of audiovisual in History Teaching to walk in sync with a liberating education.